The Psychometric Assessment of the HIV/AIDS Questionnaire in the Multiple-Indicator Cluster Survey (MICS-6) - Mohtasham GHAFFARI; Yadollah MEHRABI; Sakineh RAKHSHANDEROU; Ardeshir KHOSRAVI; Hooman BAKHSHANDEH; Narjes TAVAKOLIKIA; Elham ELAHI (Tehran University of Medical Sciences, 2019)
Background: This study aimed to psychometrically assess the HIV/AIDS items of MICS-6 in the Iranian population in the effort to collect valid and reliable data regarding the Iranian culture. Methods: This methodological study is a psychometric assessment of the HIV/AIDS items in the Multiple-Indicator Cluster Survey (MICS) as the AIDS module in MICS Round 6, which includes items on awareness and stigma in people aged over 15 and examines them for their HIV test history. First, the AIDS module was translated into Persian and then translated back into English; subsequently, the psychometric properties of the Persian version were assessed. The face, content and construct validities of this version were also evaluated. The test-retest and internal consistency estimates were also used to determine the instrument's reliability, and the questionnaire was implemented in 200 samples from the target population as a pilot study. Results: The validity of the instrument was confirmed with a CVR higher than 0.78 and a CVI of 0.79. The exploratory factor analysis was performed to confirm the validity of the five factors of the MICS-6. A high internal consistency was reported with a Cronbach's alpha coefficient of 0.98 for the questionnaire as a whole and questionnaire has good validity and reliability. Conclusion: The Persian version of the AIDS module of the MICS-6 has satisfactory reliability and validity. The present findings are consistent with the results of other studies on the psychometrics of the international AIDS questionnaire.